Hormone-secreting large adrenal ganglioneuroma in an adult patient: A case report and review of literature. (February 2014) - Erem, Cihangir; Fidan, Mehmet; Civan, Nadim; Cobanoglu, Umit; Kangul, Fevzi; Nuhoglu, İrfan and Alhan, Etem
Abstract Background. Ganglioneuromas (GNs) are neural crest cell-derived tumors and rarely occur in the adrenal gland. They are usually asymptomatic and hormonally silent. The majority of cases are detected incidentally during work-up for unrelated conditions. Hormone-secreting pure adrenal GNs in adults are extremely rare. To date, only four cases have been reported in the English literature. Case report. We describe an adult case of endocrinologically active adrenal GN incidentally diagnosed in a 64-year-old male patient with history of uncontrolled hypertension. On physical examination, he had a blood pressure (BP) of 160/100 mmHg. Abdominal computed tomography and magnetic resonance imaging showed a large solid tumor (8.5 × 7.5 × 7 cm) in the right adrenal gland. Urinary levels of norepinephrine, normetanephrine, vanillylmandelic acid and dopamin were elevated, although urinary level of epinephrine was suppressed. Right adrenalectomy was performed for treatment purposes. The histological diagnosis of the resected tumor was adrenal GN. Conclusions. Hormone-secreting pure adrenal GN occurs very rarely in adults and preoperative diagnosis is difficult. Adrenal GN may present with hormonal activity such as increased secretion of catecholamines and their metabolites. There are no specific diagnostic signs and symptoms discriminating GN and pheochromocytoma. Therefore, histopathological examination need for a definitive diagnosis of adrenal GN. The prognosis after completed surgical resection without further therapy seems to be excellent. To our knowledge, the present case is the second report that describes hormone-secreting pure adrenal GN in an adult from Turkey in the English literature. We discuss this case and review the literature on this unusual entity.